Elephant movements in different human land-uses in Chobe District, Botswana - Adams, Tempe S. F.; Leggett, Keith E. A.; Chase, Michael J. (Pachyderm, 2021)
We have a limited understanding of the effects that an increasing human population and urban and agricultural development are having on elephant movements in Botswana. Elephant movements are complex because they are influenced by a wide range of location-specific variables. This study aimed to investigate how elephants move through different human-dominated landscapes in the Chobe District, Botswana. The movements of four female elephants from the Chobe District were studied over a period of 13 months using GPS collars to follow them. Annual home ranges of the elephants were calculated using both the 100% minimum convex polygon (MCP) and 95% fixed kernel (FK) methods. Additionally, general estimating equation models were used to investigate which factors influenced the elephants’ distance moved, both hourly and daily. We found the elephants’ movement behaviour was dependent on the time of day and type of land use: whether agricultural areas, protected areas or wildlife management areas, trophy hunting blocks, and multi-use zones (e.g. game management areas). Overall, all of the elephants had smaller annual home ranges ( 450-1,750 km 2 ) than seen in other studies within southern Africa, and there was a difference in seasonal movements, between individuals. Additionally, contrary to previously published studies, the elephants made larger diurnal movements than nocturnal movements. Movements were significantly different between different land-use areas, suggesting that elephants could be developing different strategies to move through differing levels of human disturbance. It is vital for any wildlife management plan that the spatial movements of key conservation species are thoroughly understood, in order to formulate informed management decisions and create an integrated land-use management plan that enables both development and elephant coexistence. Keywords Conservation, human-dominated landscapes, land-use, spatial behaviour. Résumé Nous avons une compréhension limitée des effets qu’une population humaine croissante et un développement urbain et agricole ont sur les mouvements d’éléphants au Botswana. Les mouvements des éléphants sont complexes car ils sont influencés par un large éventail de variables spécifiques à leur emplacement. Cette étude-ci visait à étudier comment les éléphants se déplacent à travers différents paysages dominés par l’homme dans le district de Chobe, au Botswana. Les déplacements de quatre éléphants femelles du district de Chobe ont été étudiés sur une période de 13 mois, en utilisant des colliers GPS pour les suivre. Les domaines vitaux annuels des éléphants ont été calculés en utilisant à la fois les méthodes du polygone convexe minimum (MCP) à 100 % et du noyau fixe (FK) à 95 %. De plus, des modèles d’équation d’estimation généraux ont été utilisés pour étudier quels facteurs ont influencé les déplacements des éléphants, à la fois horaires et quotidiens. Nous avons constaté que le comportement de déplacement des éléphants dépendait de l’heure dans la journée et du type d’utilisation des terres, y compris les zones agricoles, les zones protégées ou les Zones de gestion de la faune, les blocs de chasse aux trophées et les zones à usages multiples (par exemple, les Zones de gestion du gibier). Dans l’ensemble, tous les éléphants avaient des domaines vitaux annuels plus réduits ( 450–1,750 km2) que ceux observés dans d’autres études en Afrique australe, et il y avait une différence dans les mouvements saisonniers entre les individus. De plus, contrairement aux études publiées précédemment, les éléphants effectuaient des mouvements diurnes plus importants que des mouvements nocturnes. Les déplacements étaient significativement différents entre les différentes zones d’utilisation des terres, ce qui suggère que les éléphants pourraient développer différentes stratégies pour se déplacer à travers différents niveaux de perturbation humaine. Il est essentiel pour tout plan de gestion de la faune que les mouvements spatiaux des espèces clés de conservation soient parfaitement compris, afin de formuler des décisions de gestion éclairées et de créer un plan de gestion intégrée de l’utilisation des terres qui permet à la fois le développement et la coexistence des éléphants. Mots clés Conservation, paysages dominés par l’homme, utilisation des terres, comportement spatial.